PEMAHAMAN HADIS MENGENAI ANJURAN MEMBUNUH CICAK - Syaiful, Muhammad (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2022)
Rasulullah SAW is a prophet and apostle who should be used as a role model by humans for their behavior. Rasulullah SAW has a very commendable personality, one of which is because he has a compassionate nature to all Allah's creatures including animals. However, there is a hadith that contains a recommendation to kill an animal, namely a lizard. The lizard is said to be a fuwaisiq animal and it is recommended to kill it and even get a reward if you kill it with one, two, up to three strokes. As in the history of Muslim, Abu Dawud and Ahmad. This study aims to reveal the meaning contained in the hadith recommending killing lizards. The hadith recommending killing lizards is one of the hadiths that needs to be understood both in text and context. This hadith is widely used by Muslims as evidence to practice it in order to get a reward, but they do not understand the hadith in terms of text, context, and its relevance to today's era. This research is a literature study, this research understands the hadith about the recommendation to kill lizards textually, contextually, and its relevance to today's era so that it can be understood properly and correctly. After conducting research on the hadith recommended to kill lizards, the researchers came to some conclusions, that the hadith spoken by the Prophet about lizards was not the lizards we currently encounter in homes. However, the lizard or wazagh referred to in the editorial of the hadith is a type of large gecko. The background of the narration of the hadith is because wazagh here caused a lot of harm to human life at the time of the Prophet. one of which is that it can cause leprosy at that time. If it is correlated today, the large gecko-type lizard contains parasites that can cause various diseases. This proves that when the Prophet (saw) recommends doing something not arbitrarily, it means that there is a specific purpose or purpose that can keep mankind from harm. Keywords: al-Wazagh (Lizard), Understanding Hadith, Suggestions for Killing Lizards